The Role of High-mass Stellar Binaries in the Formation of High-mass Black Holes in Dense Star Clusters - Ambreesh Khurana; Sourav Chatterjee (The Astrophysical Journal)
Recent detections of gravitational waves from mergers of binary black holes (BBHs) with premerger source-frame individual masses in the so-called upper mass gap, expected due to (pulsational) pair instability supernovae ((P)PISNe), have created immense interest in the astrophysical production of high-mass black holes (BHs). Previous studies show that high-mass BHs may be produced via repeated BBH mergers inside dense star clusters. Alternatively, inside dense star clusters, stars with unusually low core-to-envelope mass ratios can form via mergers of high-mass stars, which then can avoid (P)PISN, but produce high-mass BHs via mass fallback. We simulate detailed star-by-star multiphysics models of dense star clusters using the Monte Carlo cluster evolution code CMC , to investigate the role of primordial binary fraction among high-mass stars (≥15 M _⊙ ) on the formation of high-mass BHs. We vary the high-mass stellar binary fraction ( ${f}_{{\rm{b}},15}^{{′} }$ ) while keeping all other initial properties, including the population of high-mass stars, unchanged. We find that the number of high-mass BHs, as well as the mass of the most massive BH formed via stellar core collapse are proportional to ${f}_{{\rm{b}},15}^{{′} }$ . In contrast, there is no correlation between ${f}_{{\rm{b}},15}^{{′} }$ and the number of high-mass BHs formed via BH–BH mergers. Since the total production of high-mass BHs is dominated by BH–BH mergers in old clusters, the overall number of high-mass BHs produced over the typical lifetime of globular clusters is insensitive to ${f}_{{\rm{b}},15}^{{′} }$ . We study the differences in the demographics of BH–BH mergers and their implications for LIGO–Virgo–Kagra detections as a function of ${f}_{{\rm{b}},15}^{{′} }$ .